Microstructure and properties of Cu2O-GO/Zn biocomposites fabricated by a novel in situ wetting strategy. (August 2022) - Sun, Xiaohao; Wang, Xiao; Xu, Ying; Li, Wei; Liu, Debao
Graphical abstract: Highlights: Cu2 O-GO/Zn biocomposites fabricated by a Cu2 O-induced in situ wetting process. Enhanced interfacial bonding between rGO and Zn matrix via ZnO and CuZn4 interphase. Extremely high strengthening efficiency R were achieved in Cu2O-GO/Zn biocomposites. Suitable degradation rates were obtained for orthopedic applications. Cu2 O-GO addition endowed Cu2O-GO/Zn biocomposites with high antibacterial activity. Abstract: Biodegradable Zn-based composites have been recognized as a promising approach to develop the new generation biodegradable materials for orthopedic applications. However, the insufficient interfacial bonding between the Zn matrix and reinforcements limited the performance of Zn-based biocomposites. In this study, Cu2 O modified graphene oxide (Cu2 O-GO) sheets were employed as reinforcement to manufacture Cu2 O-GO/Zn biocomposites via spark plasma sintering (SPS) process. Due to the low Gibbs free energy in the formation of ZnO (−163.8 kJ·mol −1 ), an in situ reaction between Cu2 O and Zn matrix occurred during the SPS process, resulting in Cu and ZnO as reaction products. In the meantime, the Zn matrix could alloy with the in situ generated Cu, contributing to a Zn-Cu alloy matrix with enhanced mechanical performance. In other words, ZnO modified GO sheets reinforcing Zn-Cu matrix biocomposites were achieved by a one-step process. Intimate and strong interfacial connections between the graphene and Zn-Cu matrix were achieved in 4Cu2 O-GO/Zn biocomposites via ZnO-related and CuZn4 -related interfacial bonding. Considerable strengthening efficiencies (13.9–27.9) were confirmed in Cu2 O-GO/Zn biocomposites. As a result, 4Cu2O-GO/Zn biocomposites exhibited a yield strength (YS) of 222.9 MPa, a degradation rate of 68.4 mm·y −1, acceptable cytocompatibility to MC3T3-E1 cells, and antibacterial activity of 98.6% to S. aureus.